ANALISA KINERJA SISTEM HEATING DEHUMIDIFIER MENGGUNAKAN AC SPLIT UNTUK PENGERINGAN IKAN - Kurniawan, Yudhy; Ruslani, Ruslani; Akbar Anggriawan, Fadil (Jurnal Teknologi Terapan, 2017)
One of great potential area in the fisheries sector in West Java province is Indramayu District. Percentage of fisheries production which accounts for 60% of the needs of the fishery. Indramayu community, especially the northern coastal areas of Indramayu district of livelihood relies heavily on the this sector. During this process the dried fish production still relies on the natural conditions of the solar thermal. So that when the rainy season the fishermen feel a loss, because of natural heating hampered and finally ignored orders from customers due to the  and declining fish quality, so prices soaring sales doubled. Hence, the need for attention to improving the quality of production of dry fish processing, is one of the way by utilizing the split Air Conditioning (AC) as a heating dehumidifier for drying fish. This equipment is modified by utilizing the waste heat from the condenser as reheat is then added to the electric heater is controlled according to the needs drying, and after that it was blown with using  fan/blower to the drying chamber containing the fish on the shelves are arranged. The results obtained can be analyzed on the performance, drying temperature and relative humidity (RH) or water content is as expected.